2017
DOI: 10.1074/jbc.m117.778506
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphogenetic protein 9 (BMP9) and BMP10 enhance tumor necrosis factor-α-induced monocyte recruitment to the vascular endothelium mainly via activin receptor-like kinase 2

Abstract: Bone morphogenetic proteins 9 and 10 (BMP9/BMP10) are circulating cytokines with important roles in endothelial homeostasis. The aim of this study was to investigate the roles of BMP9 and BMP10 in mediating monocyte–endothelial interactions using an in vitro flow adhesion assay. Herein, we report that whereas BMP9/BMP10 alone had no effect on monocyte recruitment, at higher concentrations both cytokines synergized with tumor necrosis factor-α (TNFα) to increase recruitment to the vascular endothelium. The BMP9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 67 publications
3
36
0
Order By: Relevance
“…Consistent with our present findings, BMP9 treatment has been found to improve aberrant alveolar development and reduced lung inflammation and fibrosis but did not improve aberrant vascularization (arterial medial wall thickness and muscularization) and right ventricular hypertrophy 37 . In line with this notion, BMP9 and BMP10 can synergize with TNFα to induce the upregulation of endothelial selectins and adhesion molecules and the secretion of various key pro-inflammatory mediators 38,39 , and are therefore likely to contribute to the proinflammatory signature of the dysfunctional endothelium in PAH 40 .…”
Section: Discussionmentioning
confidence: 76%
“…Consistent with our present findings, BMP9 treatment has been found to improve aberrant alveolar development and reduced lung inflammation and fibrosis but did not improve aberrant vascularization (arterial medial wall thickness and muscularization) and right ventricular hypertrophy 37 . In line with this notion, BMP9 and BMP10 can synergize with TNFα to induce the upregulation of endothelial selectins and adhesion molecules and the secretion of various key pro-inflammatory mediators 38,39 , and are therefore likely to contribute to the proinflammatory signature of the dysfunctional endothelium in PAH 40 .…”
Section: Discussionmentioning
confidence: 76%
“…ALK1 and ALK2 type I receptors might indeed have different signaling properties. Supporting this, complementary actions of ALK1 and ALK2 mediate the BMP9/BMP10 effects in human aortic endothelial cells, enhancing TNF-α-induced monocyte recruitment to vascular endothelium [36]. Interestingly, a BMP6 mutant specifically defective in ALK2 binding but with normal affinity for ALK3 and ALK6 was not able to induce alkaline phosphatase expression, a target of p38MAPK [37], highlighting a key role for ALK2 on p38MAPK activation.…”
Section: Discussionmentioning
confidence: 83%
“…Accordingly, it has been shown that sEng can modulate integrin-mediated cell adhesion involving membrane-bound endothelial endoglin ( Rossi et al, 2013 , 2016 ; Ruiz-Remolina et al, 2017 ), and this function might have an impact on the active angiogenesis and vascular remodeling processes in the neovascularized retina of Eng -iKO e mice. In this regard, upon an inflammatory stimulus, leukocyte recruitment to the vasculature involves endothelial endoglin, via leukocyte integrins ( Rossi et al, 2013 ), as well as BMP9 ( Mitrofan et al, 2017 ). Because the inflammatory infiltrate of leukocytes appears to be involved in the vascular remodeling leading to AVMs in HHT patients ( van Laake et al, 2006 ; Zhang et al, 2016 ), a role for sEng in this cell adhesion-dependent process can be postulated ( Dingenouts et al, 2015 ; Rossi et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%